2000
DOI: 10.1038/sj.mp.4000720
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a novel corticotropin-releasing-hormone receptor type I antagonist on human adrenal function

Abstract: Corticotropin-releasing hormone (CRH) is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 47 publications
2
37
0
1
Order By: Relevance
“…31 This confirms previous reports demonstrating a local CRH/ACTH system in the adrenal medulla. Thus, CRH was shown to stimulate cortisol production in cortical and chromaffin cell co-cultures.…”
Section: Discussionsupporting
confidence: 82%
“…31 This confirms previous reports demonstrating a local CRH/ACTH system in the adrenal medulla. Thus, CRH was shown to stimulate cortisol production in cortical and chromaffin cell co-cultures.…”
Section: Discussionsupporting
confidence: 82%
“…These direct effects of CRF on the adrenal gland require the local presence of CRF receptors. Indeed, CRF receptors, predominantly CRF receptor 1 (CRF-R1), are found within the adrenal gland (Dave et al 1985, Udelsman et al 1986, Aguilera et al 1987, Willenberg et al 2000, Muller et al 2001. In addition, CRF-binding protein (CRF-BP), an important modulator of the concentration of free bioavailable CRF, has also been demonstrated in chromaffin cells of rat adrenal gland (Chatzaki et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Chromaffin cells express CRHR1 receptors and there is an intraadrenal CRH/ACTH system under feedback control of glucocorticoids. 12,19 Exogenous CRH preserves chromaffin cell morphology in vitro and stimulates catecholamine production in dispersed rat chromaffin and human pheochromocytoma cells. 21 Hypoxia-induced adrenal chromaffin cell changes are partially reversed with exogenous CRH.…”
Section: Molecular Psychiatrymentioning
confidence: 99%
“…[16][17][18] Recent studies demonstrated low epinephrine levels and a decrease in adrenal PNMT expression in CRH-deficient mice 4,6,7 and adrenomedullary atrophy has been reported in CRHR1 null mice. 6 CRHR1 receptors are expressed on chromaffin cells 19 and a direct action of CRH on chromaffin cell function has been described. 20,21 CRHR1 null mice are an interesting model to analyze the role of the CRH system for the functioning of the adrenal medulla.…”
Section: Introductionmentioning
confidence: 99%